Cytotoxicity and immunological responses following oral vaccination of nanoencapsulated avian influenza virus H5 DNA vaccine with green synthesis silver nanoparticles. - Jazayeri, Seyed Davoud; Ideris, Aini; Zakaria, Zunita; Kamyar, Shameli; Hassan, Moeini; Abdul Rahman, Omar (Elsevier, 2012)
DNA formulations provide the basis for safe and cost effective vaccine. Low efficiency is often observed in the delivery of DNA vaccines. In order to assess a new strategy for oral DNA vaccine formulation and delivery, plasmid encoding hemagglutinin (HA) gene of avian influenza virus, A/Ck/Malaysia/5858/04 (H5N1) (pcDNA3.1/H5) was formulated using green synthesis of sliver nanoparticles (AgNP) with polyethylene glycol (PEG). AgNP were successfully synthesized uniformly dispersed with size in the range of 4 to 18 nm with an average size of 11 nm. Cytotoxicity of the prepared AgNP was investigated in vitro and in vivo using MCF-7 cells and cytokine expression, respectively. At the concentration of − 5 log10AgNP, no cytotoxic effects were detected in MCF-7 cells with 9.5% cell death compared to the control. One-day-old specific pathogen-free (SPF) chicks immunized once by oral gavage with 10 μl of pcDNA3.1/H5 (200 ng/ml) nanoencapsulated with 40 μl AgNP (3.7 × 10− 2 μg of Ag) showed no clinical manifestations. PCR successfully detect the AgNP/H5 plasmid from the duodenum of the inoculated chicken as early as 1 h post‐immunization. Immunization of chickens with AgNP/H5 enhanced both pro inflammatory and Th1-like expressions, although no significant differences were recorded in the chickens inoculated with AgNP, AgNP/pcDNA3.1 and the control. In addition, serum samples collected from immunized chickens with AgNP/H5 showed rapidly increasing antibody against H5 on day 14 after immunization. The highest average antibody titres were detected on day 35 post‐immunization at 51.2 ± 7.5. AgNP/H5 also elicited both CD4+ and CD8+ T cells in the immunized chickens as early as day 14 after immunization, at 7.5 ± 2.0 and 20 ± 1.9 percentage, respectively. Hence, single oral administrations of AgNP/H5 led to induce both the antibody and cell-mediated immune responses as well as enhanced cytokine production.